Hepatic infarction induced by HELLP syndrome: a case report and review of the literature - Qinyue Guo; Zhengfei Yang; Jian Guo; Lei Zhang; Lan Gao; Bo Zhou; Qindong Shi (BMC, 2018)
Abstract Background HELLP syndrome is a rare disease in China, and 20% of patients with severe preeclampsia have been accompanied with HELLP syndrome, which is characterized by the presence of hemolysis, elevated liver enzymes and low platelet count. Case presentation In this case, we reported that a patient with preeclampsia was diagnosed with HELLP syndrome. Furthermore, hepatic infarction also was found via the computed tomographic (CT) images, which showed peripheral wedge-shaped inhomogeneous low attenuation in the right hepatic lobes via plain CT scan, and the low-density shadow and mottled appearance in the same areas where vessels were seen coursing through them via contrast-enhanced CT scan. Conclusions Besides typical clinical manifestations of the pregnant patient with preeclampsia, the typical laboratory evidences were elevated liver enzymes and thrombocytopenia. The abdominal CT scan showed imaging features of hepatic infarction, which was helpful to identify the rare complication of HELLP syndrome. Thus, we diagnosed a patient with HELLP syndrome with hepatic infarction, though the patient had no chance to do the liver biopsy.